From Nordic to Hispanic - Shift in a Family’s Given Names - Sippola, Eeva (Onomástica desde América Latina, 2023)
This article examines historical changes in naming practices through first names in a region of Argentina with a history of migration from Northern Europe. First names in a migrant family are used as a case study and different periods compared. The data show the use of Nordic names in the first generations, with a drastic change towards Hispanic first names from the third generation onwards. Also hybrid naming practices that combine both Nordic, Hispanic and other names are noted. The results show how first names in Misiones have shifted over time due to changes in the community and Argentinian policies, and how these practices reflect political and ideological stances.